Performance Analysis of Millimeter waves over FSO System under Fog Weather Conditions - Shakthi Murugan K H, Sumathi M (International Journal of Advanced Science and Technology, 2020)
Many research works have been oriented towards achieving higher data rates. Optical Wireless Communication (OWC) has gained a lot of importance. Millimeter waves have been coupled with Free Space Optics (FSO) to yield higher data rates and error free communication. A Radio over-FSO (RoFSO) system is designed with two different channels, each carrying 5Gbps data rate which is transmitted over 60GHz radio signal, yielding better performance to be used in 5G communication networks. The atmospheric turbulence in the form of fog is introduced and the system performance is studied in terms of Bit Error Rate (BER).